Finding early adopters – utilizing growth hacking methods in diffusion of innovations - Susi, Harri (fi=Turun yliopisto|en=University of Turku|, 2017)
In recent years, growth hacking has become increasingly popular method to extend the customer base especially in start-up companies due to their limited marketing budgets. Typically, growth hackers focus their influencing efforts on early adopter customers to get the early adapters to work as their marketing power. The focus of this study is to find early adopters using growth hackers’ methods and furthermore to explore how early adopters can be utilized in diffusion of innovations. In this study, growth hacking methods are fit into Steve Blank’s Customer Development model and Everett M. Rogers’ Diffusion of Innovations theory where customers are grouped based on their willingness to adapt new products and their impact on other customers. The study introduces a framework which enables effective usage of Customer Development model. Additionally, the study introduces approaches on how growth hacking can be utilized in Eric Ries’s ‘The Lean Startup’ model to enhance word-of-mouth marketing strategies and product development. This study consists of two case studies in which the growth hacking methods are implemented in social media platform Twitter. A customized algorithm (Python script) was used to harvest potential early adapters, and once the target group was reached marketing of upcoming information security products was directed on them. The reactions of the target group (5900 followers) on approx. 200 tweets/month were analysed and tweets associated with a major technology start-up event (Slush) were found as the most influential. The study further investigates the use of the algorithm on increasing the impact of social media account in both commercial and personal accounts. Based on the case studies this study proposes effective approaches on reaching early adapters and utilizing them in diffusion of innovations.